Outer measure analysis of topological lattice properties - Setiawati Wibisono (International Journal of Mathematics and Mathematical Sciences)
Let X be a set and ℒ a lattice of subsets of X such that ∅, X∈ℒ. A(ℒ) is the algebra generated by ℒ, M(ℒ) the set of nontrivial, finite, normegative, finitely additive measures on A(ℒ) and I(ℒ) those elements of M(ℒ) which just assume the values zero and one. Various subsets of M(ℒ) and I(ℒ) are included which display smoothness and regularity properties.